2010
DOI: 10.1093/nar/gkq262
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Cdc6 inhibits DNA replication and suppresses Cdc7-mediated phosphorylation of Mcm2–7 complex

Abstract: Mcm2–7 is recruited to eukaryotic origins of DNA replication by origin recognition complex, Cdc6 and Cdt1 thereby licensing the origins. Cdc6 is essential for origin licensing during DNA replication and is readily destabilized from chromatin after Mcm2–7 loading. Here, we show that after origin licensing, deregulation of Cdc6 suppresses DNA replication in Xenopus egg extracts without the involvement of ATM/ATR-dependent checkpoint pathways. DNA replication is arrested specifically after chromatin binding of Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…We found that FACT associates with chromatin in at least two distinct phases: an initial binding phase unrelated to DNA replication events and a second phase of chromatin binding that initiated after origin licensing. Initially loaded FACT is susceptible to removal from licensed chromatin but not from unlicensed chromatin, and the later association of FACT is inhibited if DNA replication is blocked before origin !ring by the addition of Cdc6 [24]. Our results also suggest that FACT binding after origin licensing is necessary for the efficient replication of eukaryotic chromatin.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…We found that FACT associates with chromatin in at least two distinct phases: an initial binding phase unrelated to DNA replication events and a second phase of chromatin binding that initiated after origin licensing. Initially loaded FACT is susceptible to removal from licensed chromatin but not from unlicensed chromatin, and the later association of FACT is inhibited if DNA replication is blocked before origin !ring by the addition of Cdc6 [24]. Our results also suggest that FACT binding after origin licensing is necessary for the efficient replication of eukaryotic chromatin.…”
Section: Introductionsupporting
confidence: 52%
“…Interphase extracts were prepared as described previously [3,24,25]. Xenopus egg extracts were supplemented with 250 "g/ml cycloheximide, 25 mM phosphocreatine, and 15 "g/ml creatine phosphokinase before use.…”
Section: Methodsmentioning
confidence: 99%
“…S8). p53 (TP53) contributes to CDC6 inhibition 24 , which results in a decreased binding affinity to origin-recognition complexes (ORC), and the formation of the pre-replication complexes (pre-RC), followed by the recruitment of the DNA replicative helicase MCM complex 25 . In addition, the phosphorylation of POLA and MCM protein binding at pre-RC is decreased as a result of the decreased transcript or protein expression of the CDC7/DBF4 complex 26 , and these interaction flows reflect the impairment of normal DNA replication processes.
Figure 5Regulatory network model of DNA replication coupled with nicotinamide.
…”
Section: Resultsmentioning
confidence: 99%
“…Cdc6 inhibits helicase activation by blocking Cdc7-mediated phosphorylation of the MCM helicase (26). We hypothesized that the Cdc6-mediated increase in MCM chromatin loading was associated with an inhibition of helicase activation.…”
Section: Resultsmentioning
confidence: 99%
“…ORC subsequently binds Cdc6 (22) and Cdt1 (23), leading to recruitment of the minichromosome maintenance (MCM) helicase (24), which is a hexamer consisting of MCM2 to 7, that functions to unwind DNA during replication (25). However, Cdc6 and Cdt1 inhibit activation of the MCM helicase until the start of S phase (26), when Cdc6 is phosphorylated by S phase CDKs, leading to its nuclear export and degradation (27, 28). Inactivation of Cdc6 and Cdt1 allows Cdc7 to phosphorylate the MCM helicase at the start of S phase (29), leading to its activation.…”
Section: Introductionmentioning
confidence: 99%